Negotiating the draft Comprehensive Convention on International Terrorism: major bones of contention - Hmoud, Mahmoud (Journal of international criminal justice, 2010)
Negotiating a Comprehensive Convention on International Terrorism has been a long and intense process. The legal regime to be created by this instrument has significant legal and political consequences. The main issues, which would frame such consequences, are how to define the crime and decide the scope of application of such a Convention. These have proven to be problematic, as negotiators have revisited issues that have been a source of debate for years, even centuries. Who has the right to participate in an armed conflict without being described as a terrorist by the Convention? To what extent do we allow the overlap between international humanitarian law and the Convention's law, if any? Do military forces have the right to be outside the scope of the Convention even in peace time? These are the main questions that the negotiators have been trying to answer in order to reach a compromise that will satisfy all parties. If genuine political will exists to conclude the Comprehensive Convention, there is no absence of legal answers that can guarantee an effective law enforcement instrument against international terrorism, without infringing on legal rights and positions under international law